Sarcopenia is associated with mortality in patients with COVID-19 independent of other demographic risk factors - Erkan, Merve; Atasoy, Dilara; Sayan, Halil Erkan; Topal, Dursun; Güneş, Mutlu (The European Research Journal, 2023)
Objectives: To investigate whether sarcopenia had an effect on in-hospital mortality independent from other demographic characteristics in patients with Coronavirus disease 2019 (COVID-19), and to determine a reliable cut-off value for sarcopenia if there is such a relationship. Methods: A total of 302 patients with COVID-19 were included in the study. Sarcopenia was assessed by indexed skeletal muscle mass at T12 vertebrae level (T12-SMI) on initial chest computed tomography (CT). A receiver operating characteristic (ROC) curve analysis was performed to detect a cut-off value of T12-SMI for mortality prediction. Then, sarcopenia was diagnosed by this value. Multivariable logistic regression analysis was used to detect independent variables for mortality. Results: Patients were separated into groups; 26 (8.6%) patients in the mortality group and 276 (91.4%) patients in the no-mortality group. In ROC analysis, cut-off values of 34.06 cm²/m² (sensitivity: 70%, specificity: 77%) in males and 29.36 cm²/m² (sensitivity: 67%, specificity: 69%) in females for T12-SMI were computed for mortality prediction. There were 110 (36.4%) patients with sarcopenia. Sarcopenia was more frequent in the mortality group than the no-mortality group (73.1% vs 33%, p < 0.001). In multivariate analysis age, previous cardiovascular and respiratory disease, and sarcopenia were independently associated with mortality in COVID-19 patients. Conclusions: A cut-off value of 34.06 cm²/m² in males and 29.36 cm²/m² in females for T12-SMI can be used to diagnose sarcopenia in patients with COVID-19. Sarcopenia is clearly associated with mortality in these patients.